The Politics of Parliamentary Restoration and Renewal: Decisions, Discretion, Democracy. Issue 1 (22nd June 2017) - Flinders, Matthew; Cotter, Leanne-Marie; Kelso, Alix; Meakin, Alex
Abstract: An extensive literature on aversive constitutionalism and elite blockages outlines the manner in which embedded political elites will generally reject or dilute reform agendas that threaten their privileged position within a constitutional configuration. It is for exactly this reason that the same seam of scholarship frequently highlights the role of crises in terms of providing a 'window of opportunity' through which a significant or fundamental recalibration of a political system may be achieved. 'The Palace of Westminster' the Joint Committee on Restoration and Renewal (R&R) concluded in September 2016 'faces an impending crisis which we cannot possibly ignore'. Their recommendation was that the Palace be completely vacated for five to eight years so that a multibillion-pound programme of rebuilding work can be undertaken. This article offers the first research-based analysis of the 'Scoping & Planning' stage (2012–2016) and reveals the 'hidden politics' of R&R in the sense of how it threatens both the British Political Tradition and the position of the two main parties. This explains the nature of the very closed and secretive decision-making processes that have characterised this stage and why a number of formative decision-making points that have been deployed to frame and restrict the reform parameters.